Clinical Characteristics and Follow-Up of 19 Children With Hashimoto’s Thyroiditis Aged Below 3 Years: A Single-Center Retrospective Analysis - Tang, Shi; Yang, Min; Zhang, Dan; Tong, Ya-jie; Xin, Ying (Frontiers in Endocrinology, 2021)
Aim: To analyze the clinical characteristics of Hashimoto’s thyroiditis (HT) in children below 3 years of age in order to improve the understanding of the disease, avoid misdiagnosis, and achieve early diagnosis and treatment. Methods: The study retrospectively analyzed the clinical data of 19 patients diagnosed with HT in the first three years of life. Results: The patients (12 female, 7 male) had an average age of 26.1 ± 8.2 months (range 10–36 months). At presentation, one patient had euthyroidism, ten had hypothyroidism, seven had subclinical hypothyroidism, and one had hyperthyroidism. The most common reasons for doctor’s visits were thyroid enlargement (21.1%), global developmental delay (21.1%), and routine thyroid function tests in patients with type 1 diabetes (26.3%). Sixteen patients provided follow-up data, and the mean follow-up time was 23.31 ± 16.44 months (range 1–48 months). In the hypothyroidism group, one patient stopped levothyroxine (LT4) treatment after 2 months; the remaining patients had been treated with LT4 since their diagnosis. In the subclinical hypothyroidism group, one patient whose thyroid function returned to normal after 1 month of being diagnosed was not treated. The remaining patients received LT4 treatment at their diagnosis or during follow-up. The patient with hyperthyroidism was treated with methimazole after diagnosis, but treatment was discontinued 11 months later and LT4 was initiated 26 months after diagnosis. One in four patients with global developmental delay approached normal mental development after LT4 treatment. Four in six patients with short stature achieved height catch-up. Conclusion: At their initial HT diagnosis, most of the children showed hypothyroidism or subclinical hypothyroidism. Children with global developmental delay require continual screening, even if the thyroid function is normal after birth, to determine whether they have HT-induced hypothyroidism. Thyroxine replacement could partially relieve the clinical manifestations of hypothyroidism and early diagnosis and treatment are essential for improving patient prognosis.